TRANSFORMATIVE LEGAL EDUCATION IN THE SOUTH AFRICAN CONTEXT (The Pretoria Student Law Review, 2021)
The late former Justice of the Constitutional Court of the Republic of South Africa, Pius Langa, opined that a truly transformative South Africa requires a new approach that places the Constitutional dream at the very heart of legal education. This view is consistent with section 29 of the Constitution which guarantees everyone the right to further education. However, the state has failed to make further (or tertiary) education progressively available and accessible. We believe this can be attributed to the fact that the South African legal education is still riddled with inequalities from the apartheid/colonial era. This article argues that decolonisation of legal education will begin when teachers of the law become cognizant of the reality that their teaching models will shape the future legal landscape, thus it is imperative for law schools to birth law graduates with an unwavering appreciation and willingness to implement constitutional values, such as human dignity and equality in practice. The advancement of these values is enhanced by the Africanisation of legal education which will ultimately legitimize the legal order so that it mirrors the society in which it exists.
Keywords: Transformative legal education; transformative constitutionalism; pedagogy